Abstract P804: Lopsided Blood-Thinning Drug Increases the Risk of Internal Flow Choking and Shock Wave Generation Causing Asymptomatic Stroke - V R, Sanal Kumar (Stroke (1970), 2021)
IntroductionConsequence of lopsided blood-thinning-drug, lowering blood-viscosity (BV), is bleeding and very frequently asymptomatic-hemorrhage (AH) and the acute-heart-failure (AHF) happen. V.R.S.Kumar et al. (2020) reported that such asymptomatic episodes are due to the internal flow choking in the cardiovascular system (CVS) at a critical blood pressure ratio (BPR), which is regulated by biofluid/blood heat capacity ratio (BHCR). MethodsThe closed-form-analytical-methodology is used for correlating BV, BPR, BHCR, vessel geometry and ejection fraction (EF). In vitro method is used for the BHCR estimation of healthy subjects. In silico method is used for demonstrating the Sanal flow choking. ResultsThe analytical models reveal that the relatively high and low BV are risk factors of internal flow choking. In vitro study shows that N2, O2, CO2 & Ar gases are predominant in fresh-blood samples of the healthy subjects at a temperature range of 37-400 C (98.6-1040 F), which increases the risk of flow-choking. In silico results demonstrated the Sanal flow choking followed by the shock wave generation and pressure-overshoot in a simulated artery with the divergent/bifurcation region. ConclusionsAn overdose of blood-thinning drug reduces BV and increases Reynolds number causing high-turbulence leading to the Sanal flow choking. Asymptomatic stroke could be diminished by concurrently lessening the BV and flow turbulence by rising thermal tolerance level in terms of BHCR or by decreasing the BPR. In conclusion, BPR must always be lower than 1.8257 as dictated by the lowest BHCR of the evolved gas (CO2) for prohibiting asymptomatic stroke.